Avaliação da biodiversidade de bactérias não cultiváveis associadas a anofelinos e seu habitat - Oliveira, Marta Rodrigues de (2015)
Malaria is a parasitic disease responsible for millions of deaths annually around the world. Its main vector in Brazil is Anopheles darlingi, Root, 1926. According literature, these vectors are found associated with a great diversity of microorganisms, most of them acquired during immature phase through larvae feeding. Bacteria whose can interfere directly on vetorial capacity of the mosquito highlights these microorganism, and its interaction with immature forms from these vectors in their breeding sites is a relevant factor for stablishing important strategies on transmission control of this disease. Therefore, considering there are no studies about microbial biodiversity associated to A. darlingi larvae and its aquatic habitat, especially on Amazon region, this work has as objective characterize bacterial microbiota associated to these species and its natural and/or artificial breeding sites, in the state of Amazonas-AM. It was collected larvae samples from the water of breeding sites of A. darlingi in the State of Amazonas. DNA extraction from larvae samples was performed through innuPREP Plant DNA® kit, and water samples were submitted to heat shock for cellular lysis. After Genomic DNA extraction, amplification of 16S gene from rDNA was performed, through 27F (5’AGAGTTTGATCMTGGCTCAG-3’) and 1100R (5’-AGGGTTGCGCTCGTT-3’) primers. Amplified products were sequenced, and taxonomic identification was performed by comparison of obtained sequences versus database sequences of 16S rRNA RDP II through Classifier program.16S rRNA region sequencing from 37 samples of 4ºestadio larvae and of water from breeding sites of A. darlingi, generated 827.842 sequences which were grouped into 6.714 bacterial OTUs (Operational Taxonomic Unities). To perform Taxonomical analysis the 20 most significant OTUs were selected, and showed more than 10.000 sequences. From these, it was identified 11 genera, 11 families, 8 orders, 7 classes belonging to Actinobacteria, Bacteroidetes, Firmicutes, Verrucomicrobia e Proteobacteria phyla. Proteobacteria phylum was the most predominant, being present in 80% of analyzed OTUs. Thus, it is shown that A. darlingi and its aquatic habitat hosts a rich bacterial diversity. Keywords: Anopheles darlingi, Biodiversity, Bacterias.